Case studies on efforts to digitalize payments in agri-food value chains - Wagner, Julia; de Brauw, Alan; Bloem, Jeffrey R.; Ambler, Kate (International Food Policy Research Institute, 2025)
Agriculture remains the backbone of rural economies across much of both Sub-Saharan Africa and South and Southeast Asia, employing 54 and 43 percent of the workforce, respectively, and providing livelihoods for most of the rural poor (GSMA, 2020; Nair and Varghese, 2020). Yet, financial transactions in agri-food value chains continue to rely overwhelmingly on cash. The 2021 Global Findex survey finds that most adults in low- and middle-income countries who were paid for agricultural products received their payment in cash. On average, one in four recipients, and fewer than one in six in Sub-Saharan Africa, received agricultural payments into an account (Nair and Varghese, 2020; Demirgüç-Kunt et al., 2022). This reliance on cash introduces a range of inefficiencies and risks, including high transaction costs, security vulnerabilities, lack of transparency, and exclusion from formal financial services (BTCA, 2023a). Digitalizing agricultural payments offers a promising solution to these challenges. Digital financial ser vices (DFS) for the agriculture sector, including mobile money, e-wallets, digital banking, digital credit, savings products, insurance, and e-commerce solutions tailored to agricultural value chains, can facilitate safer, faster, and more transparent transactions while simultaneously connecting farmers and intermediary actors to broader financial ecosystems (GSMA, 2020). By digitalizing payments, farmers can build verifiable financial histories that enable access to formal credit and insurance markets, manage income more effectively, and reduce the risks associated with cash handling. For agribusinesses, digital payments offer substantial operational efficiencies: they lower cash handling costs, improve procurement transparency, support traceability initiatives crucial for compliance with international sustainability standards, and enhance supplier loyalty through faster and more reliable payment processes (Beaman et al., 2014; Nair and Varghese, 2020; BTCA, 2023a).